2017
DOI: 10.1016/j.jaridenv.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' perceptions of climate variability and its adverse impacts on crop and livestock production in Ethiopia

Abstract: This article explores farmers' perceptions of the manifestations of climate variability and its effects on the agricultural production in selected highland areas of Ethiopia. Primary Data was collected using group and individual interviews, overt observation and a survey. Temperature and rainfall data was collected from NMSA. The study shows that more that eighty percent of farmers perceived the manifestations and effects of climate variability. The study reveals that sex, age, income and educational level are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 21 publications
9
54
0
3
Order By: Relevance
“…Our respondents' perceptions of changes in the timing of precipitation in particular had important implications for their farming activities. Both these findings are consistent with an Ethiopian study reported by Yayeh Ayal and Leal Filho (2017) and a meta-analysis carried out by Savo et al (2016). They also reinforce the importance of climate as part of the lived environment (Taylor 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Our respondents' perceptions of changes in the timing of precipitation in particular had important implications for their farming activities. Both these findings are consistent with an Ethiopian study reported by Yayeh Ayal and Leal Filho (2017) and a meta-analysis carried out by Savo et al (2016). They also reinforce the importance of climate as part of the lived environment (Taylor 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Male farmers' perception is aligned with meteorological data, which might be related to their better position to access information and primary responsibility to engage in farming activities. Proper recognition of changes in climate variables is based partly on the number of years of farming experience, meaning that older-age farmers have a more accurate perception than younger farmers [20,50]. Given the complexity of properly observing trends in weather conditions on the one hand and less reliance on traditional weather forecasts in the study areas on the other hand, higher social capital and exposure to mass media facilitate farmers' access to credible information that helps them form a correct perception of changes in local weather conditions [51].…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained from the Eurobarometer analysis show how although so many people are concerned about climate change, environmental issues, food security, and sustainability, more of them not doing what is necessary to address these challenges. Some observers suggest that this is motivated by a climate change denier-believer debate in which politics could defend skepticism as a mechanism to reject climate science [119]. In a number of societies, views about climate change divide sharply along partisan lines.…”
Section: Discussionmentioning
confidence: 99%